Avaliação da toxicidade e farmacocinética do Trachylobano-360, um diterpeno isolado de Xylopia langsdorffiana St. Hil. & Tul. (Annonaceae) - Pita, João Carlos Lima Rodrigues (2014)
Evaluation of the pharmacokinetic and toxicological profile is essential in the study of new drugs. However, these studies are rare and have been performed, in many cases, after the onset of clinical studies. Trachylobane-360 (T-360), a diterpene ent-7-acetoxytrachyloban-18-oic acid, obtained from Xylopia langsdorffiana, shows antitumor and spasmolytic activities, making it a promising molecule. Moreover, there are no reports on the toxicological and pharmacokinetic studies of this natural product. Considering all these aspects, the present study aimed to evaluate the toxicity and pharmacokinetics of T-360. In the acute toxicity test in mice, the T-360 showed low toxicity at doses of 50 mg/kg (i.v.), and 300 mg/kg (i.p.), showing no significant behavioral and haematological changes. However, the dose of 300 mg/kg (i.v.) caused death in four out of six animals (LD50 of 200 mg/kg). T-360 was not genotoxic in micronucleus assay, because it does not increase the frequency of micronucleated erythrocytes of mice treated with 25, 150 and 300 mg/kg (i.p.). Among the appropriate bioanalytical techniques for pharmacokinetic study highlights the high performance liquid chromatography coupled to mass spectrometry (HPLC/MSn). A HPLC/MSn method developed consisted of ESI ionization, in negative mode, basifying the medium, with detection of molecular ion 359 m/z. The fragmentation study showed that the ion 359 m/z is fragmented into 299 m/z, which is used to detect T-360. The best chromatographic conditions were established: C18 column under isocratic elution with mobile phase consisting of H2O:MeCN (65:35) and 0.1% of NH4OH in the aqueous phase. In method developing of extracting the T-360 in whole blood was evaluated influences the type of extracting solvent and different times and centrifugation forces. T-360 was better recovered (37.02%) of the blood matrix using CHCl3 and 14,000 xg for 15 min, showing the matrix effect and efficiency of the extraction process of -51.23% and 18.05 %, respectively. After optimization of the method, repeating the procedure and acidifying the sample, there was an increase recovery of T-360 (49.47%), reduction of matrix effect (-37.60%) and increase the efficiency of the process extraction (32.24%). In the validation of analytical method for quantification of T-360 in whole blood, using the Riparina I as internal standard (PI), the method presented himself as selective/specific, linear over the concentration range evaluated, accurate and precise. Moreover, presented limit of detection and quantification of 50 and 100 ng/mL, respectively. Finally, pharmacokinetic parameters were obtained by applying the validated method to samples of blood collected from mice subjected to treatment with T-360 at a dose of 25 mg/kg (i.v.), Obtaining the following results: Cmax of 321,34 μg/mL, t1/2 of 3,89 min, Ke of 10,68 h-1 CLs of 830,97 mL/h/kg and Vd 0,08 L/kg, which characterizes tissue distribuition. From the data analysis, it can be suggested that the T-360 continues to be a promising molecule having low toxicity. Furthermore, the pharmacokinetic results propel the continued investigation of other parameters, using other routes of administration, and the study of metabolites responsible, at least in part, by anti-tumor activity.